Microsatellite loci isolation from river buffalo using enriched partial genomic libraries - Rodrigues Venancio, L. P. [UNESP]; Amaral, M. E. J. [UNESP]; Schneider, M. P. C.; Silva, A. L. (Pagepress Publ, 2007)
The extensive use of buffalo in agriculture, especially in developing countries, begs for genetic resources to evaluate and improve traits important to local and regional economies. Brazil presents the largest water buffalo populations in the New World, with 1 1 million heads including swamp and river types. To design rational breeding strategies for optimum utilization and conservation of available genetic variability in the Brazilian buffalo's population, it is essential to understand their genetic architecture and relationship among various breeds. This depends, in part, on the knowledge of their genetic structure based on molecular markers like microsatellites. In the present study, we developed six enriched partial genomic libraries for river buffalo using selective hybridization methods. Genomic DNA was hybridized with six different arrays of repeat motif, 5' biotinylated - (CA)(15), (CT)(15), (AGG)(8), (GAAA)(8), (GATA)(8), (AAAAC)(8) - and bound to streptavidin coated beads. The cloning process generated a total of 1920 recombinant clones. Up to date, 487 were directly sequenced for the presence of repeats, from which 13 have been positive for presence of repeats as follows: 9 for di-nucleotide repeats, 3 for tri-nucleotide repeats and 1 for tetra-nucleotide repeat. PCR primer pairs for the isolated microsatellites are under construction to determine optimum annealing temperature. These microsatellites will be useful for studies involving phylogenetic relationships, genome mapping and genetic diversity analysis within buffalo populations worldwide.
Keywords: Microsatellites isolation; Enriched partial genomic libraries; River buffalo